International journal of sports science & coaching.
The journal will integrate theory and practice in sports science, promote critical reflection of coaching practice, and evaluate commonly accepted beliefs about coaching effectiveness and performance enhancement. Open learning systems will be promoted in which: (a) sports science is made accessible to coaches, translating knowledge into working practice; and (b) the challenges faced by coaches are communicated to sports scientists